2011
DOI: 10.1007/s11250-011-9858-5
|View full text |Cite
|
Sign up to set email alerts
|

Awassi sheep reproduction and milk production: review

Abstract: Awassi is the local breed of sheep in Jordan and is the most important breed in the semi-arid regions of the near east countries. Awassi ram and ewe lambs reach puberty at around 8 and 9 months of age, respectively. The breeding season of Awassi ewes starts as early as April and lasts through September. After puberty, Awassi rams are sexually active throughout the year. The normal estrous cycle in Awassi ewes is 15-20 days (average 17 days). Estrus ranges from 16-59 h (average 29 h) during the breeding season.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…The average length of the estrous cycle was comparable with observations made on other breeds [27], [28]. The differences in length of the cycle between the studies could be due to phase of the breeding season age of the sheep groups and breed differences [29].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The average length of the estrous cycle was comparable with observations made on other breeds [27], [28]. The differences in length of the cycle between the studies could be due to phase of the breeding season age of the sheep groups and breed differences [29].…”
Section: Discussionsupporting
confidence: 80%
“…The differences in length of the cycle between the studies could be due to phase of the breeding season age of the sheep groups and breed differences [29]. The mean duration of estrus for both groups was within the range reported in previous studies [27], [30]. However, there are some other studies in which a longer or shorter duration of estrus has been reported than that found in the present study [31], [32], [33].…”
Section: Discussionsupporting
confidence: 68%
“…Awassi is a multipurpose fat-tailed sheep breed with high adaptability and is one of the most widespread breeds in the Middle East and Southwest Asia (3,25). The Awassi breed has been raised in South-eastern Anatolia, Syria, Iraq, Israel.…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous to West Asia, Awassi sheep excel in milk and meat production, and are an important component in the livelihoods of many resource-poor farmers across the Middle East (Talafha & Ababneh, 2011). Moreover, Awassi sheep have been exported from their original home tract in east of the Mediterranean to more than 30 countries in all continents (Galal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%